BM232 dean's list appreciation night - Andrew, Leviana (Universiti Teknologi MARA, Sarawak, 2017)
The BM232 Dean's List Appreciation Night was held on 21 May 2017 at the Sarawak Golf Club to celebrate the excellent academic achievements of 38 students in the September 2016 - January 2017 semester examination. The dinner was officiated by the then Ketua Pusat Pengajian, Office Systems Management and Technology, Puan Noor Shima binti Antony representing Puan Norzaihan Binti Hashim, Ketua Pusat Pengajian Business and Management. At this dinner themed "Glitz and Glam”, a dinner talk entitled "Reality Shock at the Workplace” was delivered by Miss Mahirah Mamat, a Human Resource Executive at PNB Development Sdn. Bhd. In addition to sharing about the working environment, she stressed that future employees should set targets to advance their careers. She also emphasized that fresh graduates should not be too eager to buy new cars and smartphones but to save money for health insurance, buy properties such as houses and prepare for unemployment due to the economic downturn. After the Dean’s List Appreciation ceremony, the crowd stood up and cheered for Associate Professor Pauline Achan who would be retiring soon. The night was filled with energetic performances from the organizing committee (G’Amor - semester 4 students), singing by Miss Noorhaizah binti Abdul Raup, a student from the Faculty of Administrative Science, hip hop dance by Mr. Hanis bin Ahmad Zaki and beat box skills by Mr. Asil Hazmi Ayauf. Finally, the dinner ended with the announcement of the King and Queen of the Night and group photography. I would like to express my deep appreciation to the senior management of UiTM Sarawak for their support of this event every semester.